Discovering the mission of God best missional practices for the 21st century - Barnett, Mike.; Martin, Robin (Downers Grove, IL : IVP Academic, 2012)
Discovering the Mission of God explores the mission of God as expressed in the Bible, throughout church history and in cutting-edge practices being used around the world today.
Word of God and mission of God / Christopher J.H. Wright -- The missionary message of the New Testament / Joel F. Williams -- The supremacy of God in missions through worship / John Piper -- The kingdom of God and His mission / Alex Luc -- God's great commissions for the nations / Jeff Lewis -- Jesus Christ, the Living Word, and the mission of God / Bryan E. Beyer -- The heart of the task / Zane Pratt -- The church in the mission of God / Preben Vang -- The power of the Gospel / Robert L. Plummer -- The passion of Christ and the martyrs / Jerry Rankin -- The first decades of the mission of God / William J. Larkin Jr. -- The ante-Nicene church on mission / John Mark Terry -- The Gospel goes east / Zane Pratt -- Monastics on mission / Karen O'Dell Bullock -- Post-Reformation missions pioneers / R. Alton James -- The great century / Howard Norrish -- The global century / Mike Barnett -- The state of the spread of the Gospel / Jim Haney -- Finishing the task / J. Scott Holste -- Spiritual warfare and the mission of God / Jerry Rankin -- Apostles even now / Don Dent -- Strategic prayer for God's mission / Mike Barnett -- Cultures and worldviews / Stan May -- Tell his story so that all might worship / LaNette W. Thompson -- Comprehensive contextualization / A. Scott Moreau -- Effective bridging and contextualization / Kevin Greeson -- Back to basics / William R. Yount -- Church-planting movements / David Garrison -- Measuring progress in the mission of God / Gary R. Corwin -- Breaking bad missiological habits / Christopher R. Little -- Multiplying leaders on mission with God / R. Bruce Carlton -- Creative-access platforms / Tom Steffen -- Biblical lessons from the persecuted church / Nik Ripken and Kurt Nelson -- Women on mission with God / Meg Page -- Caring for God's missionaries / Robert Edwards and Nathan Evans -- The trouble with our Jerusalems / Ed Stetzer -- The local church and the mission of God / H. Al Gilbert -- Where do you fit in the mission of God? / Clyde Meador.
Includes bibliographical references.
Description based on print version record.
Keywords: Missions; Missions; RELIGION / Christian Ministry / Missions; Electronic books